ANALISIS RESIKO RETURN SAHAM TAHUNAN BANK BUMN DENGAN MENGGUNAKAN MODEL VALUE AT RISK PERIODE 2015 – 2018 - Sahang Sapta Apritchzeki (POLITEKNIK LP3I JAKARTA, 2020)
In investing, especially in the shares of companies engaged in the financial industry, it is necessary to measure the risk of these company shares. Investors are very interested in state-owned banks, so it is necessary to measure the risk. One of the benchmarks in measuring risk is the Value at Risk (VaR) model. This research is a research to see the risk of annual return of BUMN bank shares for the period 2015 – 2018.Key words: Value at Risk, Return, Risk